2018
DOI: 10.1136/annrheumdis-2017-212705
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of biologics in relapsing polychondritis: a French national multicentre study

Abstract: This study describes the efficacy of biologics for refractory RP. However, the number of complete responses was low and there were concerns about the risk of ADRs, particularly infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 13 publications
(10 reference statements)
1
42
0
2
Order By: Relevance
“…Responses of RP patients to TCZ treatment have varied; in one case report, a sustained response was shown by two patients [ 159 ] and others have indicated its effectiveness [ 160 , 161 , 162 , 163 ] but one report showed it to be ineffective [ 164 ]. A French multicenter retrospective cohort study with 41 patients with RP who were exposed to 105 biologics reported the efficacy of TCZ (n = 17) as well as TNFα inhibitors (n = 60) but a low number of complete responses and concerns about the risk of infection were reported [ 165 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…Responses of RP patients to TCZ treatment have varied; in one case report, a sustained response was shown by two patients [ 159 ] and others have indicated its effectiveness [ 160 , 161 , 162 , 163 ] but one report showed it to be ineffective [ 164 ]. A French multicenter retrospective cohort study with 41 patients with RP who were exposed to 105 biologics reported the efficacy of TCZ (n = 17) as well as TNFα inhibitors (n = 60) but a low number of complete responses and concerns about the risk of infection were reported [ 165 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…We favor the long‐term use of MMF in case of severe respiratory involvement, although in France it remains off‐label for RP, as for systemic lupus erythematosus, but the drug is reimbursed by Social Security when prescribed by referral centers. Biotherapies are gradually growing in their importance as treatment for RP . We now empirically propose adalimumab to patients with predominant rheumatologic manifestations unresponsive to methotrexate.…”
mentioning
confidence: 99%
“…Multiple biological agents have been tried, but due to the rarity of the condition, there are no randomised controlled trials in this field. A French national study looking at biologics in RP did not demonstrate any clear trends that would help guide use of biological agents [36].…”
Section: Discussionmentioning
confidence: 97%